Determination an empirical relation for the bulk etch rate of CR-39 with etching time and gamma irradiation dose - Yasir Yahya Kasim (College of Education for Pure Sciences, 2010)
ABSTRACT The rates of bulk etching (VB) and track etching (VT) are considered an important parameters in identifying the track profiles and its growing rate. So, this paper aims at determining an empirical relation for the bulk etch rate of CR-39 (250 µm) with etching time and - irradiation dose. A number of CR-39 detector pieces were exposed to different doses of exposure times (9-30) hrs with 3 hrs step of increasing. A KOH solution of concentration 25% and temperature (70 1)OC was used in chemical etching of the exposed and the standard pieces of the detector which have showed increasing of VB with -doses that exposed to. A fitting process of VB curves was carried out with different exposure times for used etching times, and it was found that the polynomial form is the appropriate one to estimate the constants of the suggested empirical equation for VB as it is related to the etching and -exposure time. However, the results of the suggested equation of VB have showed a good agreement with the experiment ones under the considered conditions.